The life of William Shakespeare : a critical biography - Potter, Lois. (Malden, MA : Wiley-Blackwell, 2012)
The Life of William Shakespeare is a fascinating and wide-ranging exploration of Shakespeare's life and works focusing on oftern neglected literary and historical contexts: what Shakespeare read, who he worked with as an author and an actor, and how these various collaborations may have affected his writing. Written by an eminent Shakespearean scholar and experienced theatre reviewer. Pays particular attention to Shakespeare's theatrical contemporaries and the ways in which they influenced his writing.
Born into the World -- This Man's Art and That Man's Scope -- Tigers' Hearts -- The Dangerous Year -- Our Usual Manager of Mirth -- The Strong'st and Surest Way to Get -- When Love Speaks -- You Had a Father; Let Your Son Say So -- Unworthy Scaffold -- These Words Are Not Mine -- Looking Before and After -- This Most Balmy Time -- Past the Size of Dreaming -- Like an Old Tale -- The Second Burden -- In the Mouths of Men.
Includes bibliographical references and index.
Print version record.
Keywords: Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616.; Dramatists, English -- Early modern, 1500-1700 -- Biography; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; DRAMA -- Shakespeare; LITERARY CRITICISM -- Shakespeare; Dramatists, English -- Early modern -- Biography; Electronic books